A study of morbidity profile and health seeking behaviour of inmates of selected old age homes of Bangalore city - K. C., Sreedhara; V., Raghuram (International Journal Of Community Medicine And Public Health, 2023)
Background: Assessment of the morbidity profile will help in the application of interventions, to improve the health status and the quality of life of the elderly Methods: A descriptive cross-sectional study was conducted among the inmates of selected old age homes of Bangalore city between November to December 2019 using complete enumeration with a pre-tested semi-structured questionnaire to assess morbidity profile and health seeking behaviour. Results: Majority of the study population (54.5%) was in the age group of 60-69 years followed by 80 years and above (25.5%) and 66.7% of were female. Most common morbidity identified among the elderly were Musculoskeletal disorders 100 (30.3%) followed by Diabetes 70 (21.2%), Hypertension 58 (17.6%), respiratory diseases 38 (11.5%), and Eye problems 34 (10.3%),) respectively. Majority of them 208 (63.0%) relied on Government health facilities citing free services as the common reason; whereas 122 (37.0%) approached the private sector for health assistance owing to the ease of access. Conclusions: Findings of the present study further reiterates the growing burden of chronic morbidities in the geriatric age group. It calls for programmes for creation of awareness among the elderly regarding regular medical checkups to ensure prevention and early detection of the chronic diseases.